1993
DOI: 10.1007/bf02073381
|View full text |Cite
|
Sign up to set email alerts
|

The apparent role of blood transfusions in the development of retinopathy of prematurity

Abstract: During a 30-month-period, 184 very low birth weight infants from two Liverpool neonatal intensive care units were screened for evidence of retinopathy of prematurity (ROP). Seventeen clinical variables previously considered relevant to the development of ROP, blood gas and blood pressure data over the first 7 days, and the maximum stage of ROP reached in either eye were recorded, together with the need for cryotherapy and current visual status. Ninety-two infants developed any stage of ROP and 15 required cryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 15 publications
2
49
0
Order By: Relevance
“…Sacks et al 21 found that infants weighing less than 1251 g with ROP received more replacement blood transfusions than infants without ROP by univariate analysis, but this association was not significant when controlling for oxygen therapy. Similar to our findings, Cooke et al 26 found that only gestational age and frequency of blood transfusions were independently associated with development of ROP. They reported a significant difference in median frequency of blood transfusions between 92 infants weighing less than 1500 g without ROP and 92 infants with ROP (1 vs. 7 transfusions).…”
Section: Discussionsupporting
confidence: 92%
“…Sacks et al 21 found that infants weighing less than 1251 g with ROP received more replacement blood transfusions than infants without ROP by univariate analysis, but this association was not significant when controlling for oxygen therapy. Similar to our findings, Cooke et al 26 found that only gestational age and frequency of blood transfusions were independently associated with development of ROP. They reported a significant difference in median frequency of blood transfusions between 92 infants weighing less than 1500 g without ROP and 92 infants with ROP (1 vs. 7 transfusions).…”
Section: Discussionsupporting
confidence: 92%
“…This includes prolonged unmonitored oxygen therapy, anemia, double volume exchange, packed cell volume transfusion, septicemia, apnea and ventilation [14,26,33,34]. Many studies have found erythrocyte transfusion to be an independent risk factor for ROP due to the presence of non-protein bound iron load in the plasma, a potent catalyst of oxidative injury [35][36][37]. In our study, children having septicemia, apnea, prolonged oxygen therapy and mechanical ventilation showed high frequency of ROP.…”
Section: Discussionmentioning
confidence: 99%
“…RBCTs may be associated with retinopathy of prematurity [11][12][13] , bronchopulmonary dysplasia [14,15] , acute pulmonary deteriorations [16] , necrotizing enterocolitis [17][18][19] , intraventricular hemorrhage [20] , and increased mortality [21] although these associations require cautious interpretation because of the retrospective and observational character of the underlying studies [22] . RBCTs are also associated with a minute residual risk of transmission of infectious agents [23] .…”
Section: Potential Risks and Benefits Of Rbctsmentioning
confidence: 99%